Pengaruh Model Pembelajaran Problem Based Learning pada Materi Hukum-Hukum Dasar Kimia terhadap Hasil Belajar Siswa Kelas X MAN 2 Model Palu - Lamalat, Tri Sulistiyawati; Supriadi, Supriadi; Nuryanti, Siti (Universitas Tadulako, 2018)
Research on the effect of the problem-based learning model in the basic laws of chemistry on student’s learning outcomes in class X MAN 2 Model Palu has been done. This study aimed to determine the effect of the application of the problem-based learning model in the basic laws of chemistry on student’s learning outcomes in class X MAN 2 Model Palu. The type of research was a quasi-experimental study non-randomized design with pretest-posttest control group design. The sample was conducted with a purposive sampling technique. The study sample was students in class X MIA 6 as an experimental group (n = 22) and students in class X MIA 3 as a control group (n = 22). The data testing of students' learning outcomes used a non-parametric statistical analysis, the analysis of Mann-Whitney U-Test. The research results indicated that the mean value of the experiment class was high compared to the control class, 22.61 >18.39. The statistical analysis obtained that sig. 2-tailed (0,032) ˂ 0.05 and Zcalculation (-2.149) ˂ Ztable (-1.96). The average value of the experiment class was 82.95 while the average value of the control class was 73.64. So it can be concluded that there is the effect of applying the problem-based learning model in the basic laws of chemistry on student’s learning outcomes.